Timing of moderate level prenatal alcohol exposure influences gene expression of sensory processing behavior in rhesus monkeys - Schneider, Mary L.; Moore, Colleen F.; Larson, Julie A.; Barr, Christina S.; DeJesus, Onofre T.; Roberts, Andrew D. (Frontiers in Integrative Neuroscience, 2009)
Sensory processing disorder (SPD), characterized by over- or under-responsivity to non-noxious environmental stimuli, is a common but poorly understood disorder. We examined the role of prenatal alcohol exposure, serotonin transporter gene polymorphic region variation (rh5-HTTLPR), and striatal dopamine (DA) function on behavioral measures of sensory responsivity to repeated non-noxious sensory stimuli in macaque monkeys. Results indicated that early gestation alcohol exposure induced behavioral under-responsivity to environmental stimuli in monkeys carrying the short (s) rh5-HTTLPR allele compared to both early-exposed monkeys homozygous for the long (l) allele and monkeys from middle-to-late exposed pregnancies and controls, regardless of genotype. Moreover, prenatal timing of alcohol exposure altered the relationship between sensory scores and DA D2R availability. In early-exposed monkeys, a positive relationship was shown between sensory scores and DA D2R availability, with low or blunted DA function associated with under-responsive sensory function. The opposite pattern was found for the middle-to-late gestation alcohol-exposed group. These findings raise questions about how the timing of prenatal perturbation and genotype contributes to effects on neural processing and possibly alters neural connections.